Switching Behavior and Forward Bias Degradation of 700V, 0.2A, β-Ga2O3 Vertical Geometry Rectifiers. (30th January 2019) - Yang, Jiancheng; Fares, Chaker; Ren, Fan; Chen, Yen-Ting; Liao, Yu-Te; Chang, Chin-Wei; Lin, Jenshan; Tadjer, Marko; Smith, David J.; Pearton, S. J.; Kuramata, Akito
Abstract : We report the switching recovery characteristics of large area (contact dimension 0.04 × 0.04 cm 2 ) vertical geometry β-Ga2 O3 Schottky rectifiers, consisting of Si-doped epitaxial layers on conducting bulk substrates. Devices that were switched from forward current of 0.225 A to reverse off-state voltage of −700 V in an inductive load test circuit showed a recovery time (trr ) of 82 ns, with a reverse recovery current (Irr ) of 38 mA and dI/dt of −2.28 A. μsec −1 . This shows the potential of Ga2 O3 rectifiers for power switching applications, provided effective thermal management schemes can be implemented. Devices deliberately tested to failure under forward bias conditions exhibit delamination and cracking of the Ni/Au contact and underlying epitaxial Ga2 O3 due to the low thermal conductivity of the Ga2 O3 . This failure mode is different to that under high reverse breakdown conditions, where pits formed by material failure under the high field generated at the edge of the rectifying contact occurs.